Hydrogen-bonded organic frameworks (HOFs): a new class of porous crystalline proton-conducting materials - Karmakar, Avishek; Illathvalappil, Rajith; Anothumakkool, Bihag; Sen, Arunabha; Samanta, Partha; Desai, Aamod V.; Kurungot, Sreekumar; Ghosh, Sujit K. (Angewandte Chemie-International Edition, 2016)
Two porous hydrogen-bonded organic frameworks (HOFs) based on arene sulfonates and guanidinium ions are reported. As a result of the presence of ionic backbones appended with protonic source, the compounds exhibit ultra-high proton conduction values (sigma) 0.75x 10(-2)Scm(-1) and 1.8x10(-2)Scm(-1) under humidified conditions. Also, they have very low activation energy values and the highest proton conductivity at ambient conditions (low humidity and at moderate temperature) among porous crystalline materials, such as metal-organic frameworks (MOFs) and covalent organic frameworks (COFs). These values are not only comparable to the conventionally used proton exchange membranes, such as Nafion used in fuel cell technologies, but is also the highest value reported in organic-based porous architectures. Notably, this report inaugurates the usage of crystalline hydrogen-bonded porous organic frameworks as solid-state proton conducting materials.
Keywords: guanidinium; hydrogen-bonded organic frameworks; porous crystalline frameworks; proton conduction; sulfonates